Menerapkan Perilaku Hidup Bersih Melalui Program Penyuluhan Peduli Kebersihan Diri Dan Lingkungan Bagi Anak - Rachel Br Tarigan; Erni Asneli Asbi; Fajar Utama Ritonga (Universitas Maritim AMNI Semarang, 2024)
Clean living is the beginning of a healthy life. Clean is not only limited to ourselves but also accompanied by the cleanliness of the environment in which we live. Therefore, clean living education was chosen to teach children to care more about personal hygiene and the cleanliness of their environment and through this activity is expected to support children to live healthy. Some educational activities around personal hygiene and the environment. Personal hygiene consists of cleanliness of the body, hair, nails, teeth, and hands. Environmental hygiene includes waste selection and cough etiquette. The stages of implementing activities using the social work method are general stages consisting of the stages of engangement, intake and contract, assessment, program planning, intervention, evaluation, and termination. This clean living education activity was carried out as part of the practical activities of fieldwork 2 (PKL2) of the Social Welfare Study Program.